PROMOTING ENGLISH TEACHERS’ PROFESSIONAL DEVELOPMENT (TPD) THROUGH THE PRACTICE OF LESSON STUDY - Yanuarti Apsari; Isry Laila Syathroh; Rissa San Rizqiya (IAIN MADURA, 2017)
This paper sheds some lights on the practice of lesson study conducted in higher education level in relations to teacher professional development. This study employed an explorative research design which involved a team of three English teachers of STKIP Siliwangi and one class of English Department. The team was involved in jointly designing, teaching, researching, refining a research lesson. The research was conducted in three cycles, in which each cycle was evaluated. The data were collected through two instruments: classroom observation and teachers’ reflective notes. The result revealed that the practice of lesson study can create multiple pathways for teaching improvement, especially in terms of collaborative activities done by teachers involved in the lesson study team. The result also revealed that the practice of lesson study the practice of lesson study can improve not only students’ academic skills, but also students’ social skills.